2021
DOI: 10.1186/s12944-021-01562-1
|View full text |Cite
|
Sign up to set email alerts
|

High density lipoproteins and oxidative stress in breast cancer

Abstract: Breast cancer is one of the main leading causes of women death. In recent years, attention has been focused on the role of lipoproteins, alterations of cholesterol metabolism and oxidative stress in the molecular mechanism of breast cancer. A role for high density lipoproteins (HDL) has been proposed, in fact, in addition to the role of reverse cholesterol transport (RCT), HDL exert antioxidant and anti-inflammatory properties, modulate intracellular cholesterol homeostasis, signal transduction and proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 131 publications
(166 reference statements)
0
27
0
1
Order By: Relevance
“…Secondly, metabolic markers differed pre-chemotherapy and shortly post-chemotherapy. Some studies have shown a relationship between lipid metabolism and risk for cancer, potentially mediated by activation of inflammatory pathways [62] , while whole-body metabolic influence on tumor characteristics requires further attention [63] . These baseline results emphasize the need to control for a subjects’ susceptibilities or comorbidities when investigating additional treatment effects on metabolic and/or blood cell markers.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, metabolic markers differed pre-chemotherapy and shortly post-chemotherapy. Some studies have shown a relationship between lipid metabolism and risk for cancer, potentially mediated by activation of inflammatory pathways [62] , while whole-body metabolic influence on tumor characteristics requires further attention [63] . These baseline results emphasize the need to control for a subjects’ susceptibilities or comorbidities when investigating additional treatment effects on metabolic and/or blood cell markers.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] The root cause of breast cancer is multifaceted, and the risk factors include age, early age menarche, late age menopause, first pregnancy at late age, contraceptives, diet, heredity, and prior incidences of benign breast diseases. [ 34 ] In cancer, over energy consumption of the host contributes to loss of body weight. [ 35 ] In our study, the bodyweight of the DMBA‐stimulated breast cancer animals declined compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…In hypoxic TME, HDL-C can also promote the phosphorylation of VEGFR2 to enhance angiogenesis through the p38 MAPK signaling pathway [ 37 ]. Thirdly, in addition to anti-inflammatory and immune regulation, HDL-C also has antioxidant effects, which can maintain intracellular cholesterol homeostasis, regulate signal transduction and cell proliferation, thereby being a protective factor for cancer patients [ 38 ].…”
Section: Discussionmentioning
confidence: 99%